Pengaruh Implementasi E-Procurement Terhadap Fraud Pengadaan Barang Dan Jasa Dalam Mewujudkan Good Governance - Mu’ah, Mu’ah; Masram, Masram; Amalia, Wiwik; Sayyid, Mokhtar; Mas’adah, Mas’adah (Owner : Riset dan Jurnal Akuntansi, 2024)
Public procurement of goods and services is an important part of good governance. In the procurement of goods and services, a common problem that arises in the flow of globalization and the democratization process of procurement of goods and services is inefficiency, meaning that the procurement of goods and services so far has not produced competitive prices. This study aims to test and analyze the Implementation of E-Procurement on the procurement of goods and services in realizing Good Governance (Lamongan Regency Government Study). The research was conducted at the Lamongan Regency Government. The research population used primary data sources totaling 889 people and the sample results in this study were determined using the Slovin formula, so that in this study 276 samples were obtained. The data collection method used is the questionnaire method, literature study and observation with data analysis techniques using SPSS 24.0 software using validity test, reliability test, classical assumption test, simple regression test, path analysis test, and sobel test. The overall research results show that the independent variables in this study can provide an influence on the dependent variable of research with the results showing that E-Procurement can affect fraud, E-Procurement can affect good governance, and Fraud can affect good governance, but the results of testing the mediating variable Fraud is not able to mediate the relationship between E-Procurement to good governance. The implication of this research is advice to the Lamongan Regency government to provide guidance and training to its human resources because there is still a lack of skilled personnel who are able to operate the E-Procurement system. This makes good governance practices not run well.